Pengembangan Sumber Daya Manusia Dalam Usaha Kecil dan Menengah : Kajian Konseptual - Fransisca Mulyono (Jurnal Administrasi Bisnis, 2012)
Human resource development in small and medium scale enterprises (SMEs) isknown to have a role as important as large-scale enterprises in achieving competi-tive advantage. The purpose of this paper is to provide a brief overview of humanresources development in SMEs. Management and development of human resourcesin SMEs generally done informally, i.e. do not have written rules; recruitment processdone through employees’ word-of-mouth; selection process is done based on consid-eration of small business owners; training process is determined to SME owners; andmotivation in SMEs in terms of salary or wages are often considered smaller thanlarge enterprises.Keywords: Informal human resource, recruitment and selection in SME, trainingand development in SME, Motivation in SME